The Development of Catalyst for Methanol Synthesis from Synthesis Gas - FITRYANTI HERLAMBANG (NIM : 13013102)- IVAN PUTERA (NIM : 13013090) , VANIA
Methanol production in Indonesia has not been able to meet the needs of the domestic demand so that import of methanol is still excecuted in large amount of quantities. Moreover, local methanol industry uses imported catalysts. The most widely used catalyst to produce methanol is a copper (Cu) based, alumunium (Al) supported, and zinc (Zn) promoted catalyst. One of the metals that may become a great promoter is zirconia (Zr). The goal of this research is to obtain the composition of zirconia within the CuZnO/Al2O3 catalyst in order to achieve maximum synthesis gas conversion. The feed used in this research is syngas and the reaction occurs in a pipe reactor at 523 K and 50 bar. The variation of composition of ZrO within the CuZnO/Al2O3 are 0%,10%,15%,20%, and 30% This research consists of catalyst synthesis, catalyst activity test, and catalyst characterization. The catalysts are synthesized by coprecipitation method. Then, the catalysts are tested for methanol synthesis reaction in a pipe reactor. The performance of the catalysts are represented by the reaction conversion which is analyzed by gas chromatography. Specific surface area of catalyst is characterized with BET method. With the variation of zirconia composition about 0%, 10%, dan 30 %, the surface are given by the BET analysis are 17,03 m2 g-1, 7,09 m2 g-1, dan 7,09 m2 g-1 , respectively. Catalyst activity test results in average conversion about 12,2%, 3,4%, dan 3,9%, respectively. These catalysts are also compared to the commercial one which has average conversion 22,9% and surface area 36,55 m2 g-1. Stirring process in the catalyst synthesis step results in low quality of catalyst produced in this research compared to that of the commercial catalyst. Addition of zirconia on methanol synthesis catalyst does not increase the activity of catalyst for synthesis with CO/H2=1/2 as the feed.